Estimation of shipping emissions using vessel Long Range Identification and Tracking data. Issue 2 (30th November 2017) - Alessandrini, Alfredo; Guizzardi, Diego; Janssens-Maenhout, Greet; Pisoni, Enrico; Trombetti, Marco; Vespe, Michele
ABSTRACT: Shipping is a growing source of air pollutants and greenhouse gases, which are emitted mainly over an international territory, the seas, for which only shared responsibility by all countries is felt. The international community, in particular the International Maritime Organisation, is called to look for appropriate mitigation of these emissions. This starts with the reporting of emissions in an inventory and its mapping over the international territory to be able to then evaluate the effect of emission reduction policies on the environment. Under the European Monitoring and Evaluation Programme, Member States are required to provide gridded emissions for the different sectors but the spatial allocation of ship emissions requires a supranational setup to avoid transboundary inconsistencies. By using vessel density maps extracted from historical Long Range Identification and Tracking (LRIT) data, accurate high-resolution maps of emissions can be obtained in support of policy development, implementation and monitoring in the interrelated fields of air quality and climate.